Breaking ore and gender patterns : a strategic and sustainable R&I-agenda for the Swedish mining industry - Andersson, Eira; Abrahamsson, Lena; Fältholm, Ylva; Lindberg, Malin (Luleå tekniska universitet, Arbetsvetenskap, 2013)
The Swedish mining industry experiences a major production and economic boost and Luleå University of Technology (LTU) has established itself as Europe’s leading mining university. Together they are, along with other actors in society, a leading innovation system. This innovation system, however, face a number of challenges, such as recruitment problems, demand for new technology and research, mining communities that need be upgraded and restructured and unequal, gendered work, organizations and innovation policy initiatives.In this paper we present a gender aware research and innovation agenda in the mining sector, which aims to create more gender equal innovation and thus contribute to a socially sustainable and internationally competitive development of the Swedish mining sector. The agenda, a result of interactive collaboration between the project team, LTU mining researchers and actors from e.g. LKAB, Boliden AB, Northland resources as well as The County Council of Norrbotten and the local communities, contains a list of tentative projects, defined by the innovation system. Some examples of projects are; Key roles of middle management for a gender equal mining industry, Gender patterns among mining entrepreneur companies, Gender aware and strategic recruitment, promotion and retention practices in the mining industry and Attractive and gender equal mining communities. The long-¬‐term vision, defined by the innovation system, is that the Swedish mining industry is a field of excellence, that the industry is well known for being world-¬‐class at breaking ore and gender patterns, that gender aware organizations and workplace cultures are created and sustained for efficiency, productivity and innovation as well as that regions and communities are characterized by economic growth, openness, tolerance and collaboration between mining companies and society. Drawing on theories and reflections on “undoing gender”, “degendering” and “gender toning down” we will in the paper also introduce a discussion on the ...